Kelayakan Usaha Salad Buah pada UMKM Kuliner Sehat: Tinjauan Aspek Pasar, Teknis, Manajemen, dan Keuangan - Reski Aulia Putri; Anisa, Anisa; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Cash is the most liquid asset and is highly vulnerable to errors and fraud, thereby requiring special attention in the audit process. The cash cycle audit plays a crucial role in maintaining the reliability of financial statements through the examination of internal controls and cash transactions. This study aims to analyze cash cycle audit procedures in enhancing the reliability of financial statements through a conceptual review based on relevant literature and previous studies. The research employs a qualitative approach using a literature study method, drawing on scientific journals and related academic publications. The findings indicate that the systematic implementation of cash audit procedures, including internal control testing, bank reconciliation, and substantive testing, significantly contributes to improving the accuracy and fairness of financial statements. Cash cycle audits also strengthen internal control systems while increasing the transparency and credibility of financial information. The study concludes that the cash cycle audit serves as a strategic instrument in supporting reliable and sustainable financial reporting quality.